Research on toughening mechanisms of alumina matrix ceramic composite materials improved by rare earth additive - 张希华 刘长霞 李木森 张建华 (Journal of rare earths, 2008)
Mixed rare earth elements were incorporated into alumina ceramic materials. Hot-pressing was used to fabricate alumina matrix composites in nitrogen atmosphere protection. Microstructures and mechanical properties of the composites were tested. It was indicated that the bending strength and fracture toughness of alumina matrix ceramic composites sintered at 1550 ℃ and 28 MPa for 30 min were improved evidently. Besides mixed rare earth elements acting as a toughening phase, AlTiC master alloys were also added in as sintering assistants, which could prompt the formation of transient liquid phase, and thus nitrides of rare earth elements were produced. All of the above were beneficial for improving the mechanical properties of alumina matrix ceramic composites.